A comprehensive review on water pollution, South Asia Region: Pakistan - Noor R.; Maqsood A.; Baig A.; Pande C.B.; Zahra S.M.; Saad A.; Anwar M.; Singh S.K. (Elsevier B.V., 2024)
Pakistan is one of the most water-polluted country in the South Asia Region. Drinking water is contaminated with microbial and toxic metals throughout Pakistan. The values of different parameters recommended by World Health Organization (WHO) are typically violated. Pakistan's drinking water quality is inadequately maintained and monitored, leading to threats to the health of the community. The main goal of this review is to discuss water pollution by giving an overview of the Pakistan river water pollution and the significant sources which are responsible for water pollution, a major pollutant that involved in water pollution (i.e., microbial contamination and heavy metal pollution) and the health issues from major pollutant. We have observed that the urban cities are continuing increasining the water pollution, health issues, river pollution, heavy metal pollution etc. in the Pakistan country and other parts of region. In this view, urban cities and population pressures are directly affected on the natural resources, ecosystem, fresh water demand, water quality pollution and health issues etc. The important relation of urban cites and agricultures because so many cities majour sources of pollution. In this view, so many river water polluted and water quality decrasing due to urban cites and climate changes. The waer sample were collected during the year of 20002020. The findings of this review come from several types of researches which have accepted for publication in high impact factor world class journals and national government reports. Moreover, purpose of review is to make the decision-makers, policy makers, researchers, and administration departments start the valuable steps and to create advanced strategies to ensure disinfect and pure water. There is an immediate need to take urgent measures to minimize further contamination and upgrade the already present bodies of water to save the community and atmosphere from an outbreak of worldwide diseases. 2023 Elsevier B.V.